Agricultural policies, agricultural production and rural households' welfare in Ethiopia - Zewdie Habte Shikur (Journal of Economic Structures, 2020)
The paper employs the computable general equilibrium (CGE) model of the Oromia region of Ethiopia to assess the macroeconomic impacts of agricultural policy on agricultural growth and rural households' social welfare. The analysis is based on social accounting matrix (SAM) of Oromia region. This Oromia SAM is employed as a framework to estimate the effects of policy shocks on rural households' social welfare. This SAM provides base year data needed for policy simulation in CGE model of Oromia region. This study develops two simulations based on economic assumptions and tests their effects on agricultural production, and social welfare. The first set of experiment focuses on the irrigation policies that change the factor intensities in the production of agricultural commodities, and the second one focuses on the precision agriculture that raises agricultural productivity in the use of technologies. The analysis identifies that irrigation scaling up has a positive effect on agricultural production, and social welfare. The application of precision agriculture generates a significant and positive effect on agricultural productivity and production, and rural households' income and consumption. This finding suggests that price support policy should be implemented simultaneously with suggested policies.
Keywords: 330; Agricultural policies; Agricultural production; Employment; Income and consumption